« Allez donc m’cri ane tasse d’eau » : le malaise créé par l’introduction de la langue orale dans les textes d’Albert Laberge - Caroline Loranger (Continents manuscrits)
During the 1960’s, the work of Albert Laberge, a writer of the first half of the 20th century, was rediscovered. Even if critics appreciate the body of Laberge’s work, they feel uneasy about his writing style, which could be explained by the way in which the integration in the written text of words borrowed to the spoken language was perceived at the time.